PHYSICAL ACTIVITY DURING SCHOOL RECESS AND PHYSICAL EDUCATION AMONG DEAF SCHOOL CHILDREN1 - MARTÍNEZ,Paulina Yesica OCHOA (2022)
ABSTRACT: The objective of this study was to determine comparatively the physical activity in Physical Education and school recess of hearing-impaired students in Primary Education. Fifty-eigth Physical Education classes and recess in Primary Education were evaluated in a representative way, in specialized educational institutions for people with hearing disabilities. Physical activity was determined using the system for observing fitness instruction time (SOFIT). Inferential statistics, using the Student’s t-test, reported significant differences with more moderate to vigorous physical activity performed during recess than in Physical Education. The same pattern was identified in schoolchildren without diagnosed disabilities. It is recommended that teachers guide the content for the development of coordinating skills that favor the gross and fine motor conditions of this population, implementing didactic strategies that increase the amount of moderate to vigorous activity in Physical Education that is greater than that performed during recess.